The role of non-pharmacological behavior management on the success of children's dental care: Peran behavior management non-farmakologi pada keberhasilan perawatan gigi anak - Eko Sri Yuni Astuti (Makassar Dental Journal, 2022)
The success of the dental treatment in children does not depend on mastering the basic techniques of the treatment but if can to manage the child's behavior. Children's fear and anxiety are child behaviors that can hinder the success of the treatment. The pur-pose of this paper is to discuss non-pharmacotherapy behavior management for the children. The nonpharmacologic behavior management methods are behavior shaping, tell show do (TSD), desensitization, modeling,distraction, positive reinforcement, voice control, retraining, and hand over mouth exercises (HOME). Behavior classification in healthy children due tononpharma-cologic behavior management methods approach are the Frankl classification rating 2 and 3 or the Wright clinical classification scale 2 and 3. The selection of the appropriate behavior management method will determine in the success of dental treatment in children.